The unmet travel needs of the older population: a review of the literature. Issue 4 (4th July 2017) - Luiu, Carlo; Tight, Miles; Burrow, Michael
ABSTRACT: Unmet travel needs can be defined as trips and activities that people need or would like to do more, but for a variety of reasons they are prevented from doing so. This paper provides a critical evaluation of the literature focused on unmet travel needs, with the aim of assessing the scope of existing studies on this topic and better understanding the full context of older people's mobility. This narrative review identifies how travel needs in later life have been assessed, and the barriers that affect the ability of older people to fulfil these needs. Due to the heterogeneity of older people and differences in research approaches, the analysis of the literature is not conclusive in terms of identifying the real impact of the analysed variables and measures on unrealised mobility. Nevertheless, of the studies analysed, on average at least one-third of older people report unmet travel needs. This situation was found to worsen with age, and women were reported to be more affected than men. The pursuit of leisure, and in particular visiting friends and family, was found to be the activity most associated with unmet travel needs.